Linguistic and Cultural Image of HOME among Rehabilitated Youth - Joanna KULWICKA-KAMIŃSKA; Karina SZAFRAŃSKA (Communications of International Proceedings, 2021)
Home is a concept that accompanies man at all times and in each historical epoch. It is of paramount importance not only in Europe but in all cultures’ spiritual and material heritage. ‘It determines the circle of elementary experiences of every human being and is at the very centre of the generally recognized system of values ​​– alongside such concepts as mother, family […] and homeland – with which it is connected by a network of semantic dependencies’ (Bartmiński 2006: 167). Home is one of the concepts acquired and assimilated through ‘experiencing the world’. The youth staying at the Youth Educational Centres are individuals at risk of exclusion and social dezadaptation. Recent research shows that they often experience deficits in social competencies and struggle with socialising (Wysocka, 2017). Although the YECs aim to reshape their students' attitude towards their future life, some students leave the custody of the centres with ‘warped’ preconceptions. An analysis of the linguistic picture of ‘home’ concept provides insight into the paradigm that the adolescents will adhere to while creating their own home and family, as well as their values, visions, expectations and aspirations regarding ‘home’. The following research is an attempt to present the conceptualization of HOME based on the statements of socially maladjusted youth staying in youth educational centres (YEC)1, with a primary focus on how the rehabilitated youth categorized HOME, what features they attributed to it, and as what picture it created.